Pengaruh Kualitas Pelayanan Dan Kepuasan Terhadap Loyalitas Pelanggan (Studi Usaha Kuliner di Jakarta) - Andi Heru Susanto (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
Restaurants in Jakarta is flourishing making tight competition among culinary businesses and they strive to race in winning the competition. The tough rivalry is because the business owner is striving to have service excellence, top quality and deliver customer satisfaction. Quality and customer satisfaction are the primary factors to gain customer loyalty. This will influence demand to make sure that the target customer does not look away and choose similar product. The population of the research is 150 respondents taken from restaurants spread over the five regions in DKI Jakarta. The research is using Structural Equation Modelling (SEM) method. The result indicates that service quality influence satisfaction, satisfaction influence customer loyalty and service quality influence customer loyalty.